Co-creating Sustainable Urban Futures A Primer on Applying Transition Management in Cities - Frantzeskaki, Niki.; Hölscher, Katharina; Bach, Matthew; Avelino, Flor.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This is a unique book that provides rich knowledge on how to understand and actively contribute to urban sustainability transitions. The book combines theoretical frameworks and tools with practical experiences on transition management as a framework that supports urban planning and governance towards sustainability.  The book offers the opportunity to become actively engaged in working towards sustainable futures of cities. Readers of this book will be equipped to understand the complexity of urban sustainability transitions and diagnose persistent unsustainability problems in cities. Urban planners and professionals will build competences for designing transition management processes in cities and engaging with multidisciplinary knowledge in solution-seeking processes.The heart of the book marks the variety of very different local case studies across the world - including, amongst others, Rotterdam in the Netherlands, La Botija in Honduras, Sydney in Australia and Cleveland in theUS. These rich studies give inspiration and practical insights to young planners on how to create sustainable urban futures in collaboration with other stakeholders.  The case studies and critical reflections on applications of transition management in cities offer food for thought and welcome criticism. They also introduce new lenses to understand the bigger picture that co-creation dynamics play in terms of power, (dis-)empowerment, legitimacy and changing actor roles. This will equip the readers with a deep understanding of the dynamics, opportunities and challenges present in urban contexts and urban sustainability transitions.
Forward - My experience with Transition Management -- Transition management in and for cities: introducing a new governance approach to address urban challenges -- Understanding the urban context and its challenges -- Introducing sustainability transitions' thinking in urban contexts -- Transition Management: Guiding Principles and Applications. Urban Planning and Transition Management: Rationalities, instruments and dialectics -- Empowering actors in transition management in and for cities -- "Starting up Transition Management: A closer view on the systems analysis and how it initiated transformative thinking in Ghent and Aberdeen cities" -- Transition Management in urban neighbourhoods: The case of Carnisse, Rotterdam, the Netherlands -- 9. A German experience: the challenges of mediating 'ideal-type' Transition Management in Ludwigsburg -- 10. Transition Management for local sustainability - A case study from La Botija protected area, San Marcos de Colón, Honduras -- 11. Translating transitions thinking and transition management into the city planning world --  Transition Management in Urban China: Co-creation of New Homes or a Monopoly Game?- 13. A Transition Management Approach for Shrinking Cities in the United States -- Context-driven Transition Management as a necessary vehicle for sustainable urban futures in Suriname -- Urban Transition Management as a democratic practice? The case of Rotterdam's waterfront regeneration.So what? Transition management as a transformative approach to support governance capacities of cities -- Appendix - Exercises and Exam Questions for Lecturers using this book.
Keywords: Applied ecology; Sustainability; Sociology, Urban; Architecture; Applied Ecology; Sustainability; Urban Sociology; Cities, Countries, Regions